The Protective Effect of Syringic Acid on Ischemia Injury in Rat Brain - Guven, M.; Aras, A.B.; Topaloǧlu, N.; Özkan, A.; Şen, H.M.; Kalkan, Y.; Okuyucu, A. (Turkiye Klinikleri Journal of Medical Sciences Talapapa Bulvary no. 102 Hamammonu 1 06230, 2015)
Materials and methods: The rats were randomly divided into 4 groups: control group (no medication or surgical procedure), sham group (artery occlusion), artery occlusion + syringic acid group sacrificed at 6 h, and artery occlusion + syringic acid group sacrificed at 24 h. Obtained brain tissue from the right hemisphere was investigated histopathologically and for tissue biochemistry.Results: Superoxide dismutase and nuclear respiratory factor 1 values decreased after ischemia and they increased after syringic acid treatment, while increased malondialdehyde levels after ischemia were reduced after treatment. Caspase-3 and caspase-9 values increased after ischemia and decreased after treatment; this reduction was more pronounced at 24 h.Conclusion: Our study revealed that syringic acid treatment in cerebral ischemia reduced oxidative stress and neuronal degeneration. In the light of the biochemical and histopathologic results of the present study, we think that syringic acid treatment may be an alternative treatment method.Background/aim: Brain ischemia and treatment are important topics in neurological science. Free oxygen radicals and inflammation formed after ischemia are accepted as the most significant causes of damage. Currently there are studies on many chemopreventive agents to prevent cerebral ischemia damage. Our aim is to research the preventive effect of the active ingredient in syringic acid, previously unstudied, on oxidative damage in cerebral ischemia. © TÜBİTAK.
Keywords: Apoptosis; Brain Ischemia; Oxidative Stress; Rats; Syringic Acid